2017
DOI: 10.1038/s41598-017-15845-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the anticorrosive protective mechanisms of modified epoxy coatings with improved barrier, active and self-healing functionalities: EIS and spectroscopic techniques

Abstract: The present investigation adopted long-term in-situ electrochemical and spectroscopic approaches to study the combined active, self-healing and passive protective mechanisms of a new class of innovative anti-corrosive coatings based on epoxy doped with clay nanotubes impregnated with active species for the protection of carbon steel in 3.5% NaCl solution. The suitability of the as-received clay nanotubes to encapsulate the active agents was confirmed by different spectroscopic measurements. Tube end stopper wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…In acidic media, the released MBTs were absorbed on the mild steel surfaces in their molecular or protonated form with donor–acceptor interactions between the π electrons of the MBT and the vacant d orbitals of the metal atoms . This chemisorption of MBTs resulted in the formation of a compact passive layer on the mild steel surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In acidic media, the released MBTs were absorbed on the mild steel surfaces in their molecular or protonated form with donor–acceptor interactions between the π electrons of the MBT and the vacant d orbitals of the metal atoms . This chemisorption of MBTs resulted in the formation of a compact passive layer on the mild steel surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have shown that the protective behavior of organic coatings containing S, N, and O atoms is obtained from the formation of a covalent bond between the metal and a lone pair of electrons in the functional group of organic additives . The formed passive layer of MBTs improved the bond formation between the organic additives and metal surfaces and increased the effect of the electron density . Therefore, this layer prevented from the attack of corrosion species with increasing anticorrosive and self‐healing performances of the EP/NC MBT–CeO 2 coatings.…”
Section: Resultsmentioning
confidence: 99%
“…For self‐healing and corrosion resistance tests, the coating was scribed with the help of a sharp blade, after curing for 4 days. Thus, a desired defect of approximately 100 µm wide and 10 mm long was initiated as earlier described in other literatures …”
Section: Methodsmentioning
confidence: 99%
“…For salt spray test, the coating without and with microcapsules were evaluated for their self‐healing and anticorrosion properties using salt spray corrosion method. Cross scribes were formed down to the metal surface to observe the protection action of the coatings . After a certain period, the surface of the coated sample was observed by optical microscopy (OM) and scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…EIS is used as a powerful tool to investigate the barrier properties of the coating systems developed in the current study and to assess the impact of the addition of a liquid rubber polymer either as a container surface modified or as an additive incorporated in free form in the epoxy matrix. As it has been well-documented previously in literature, the magnitude of impedance modulus at low frequency (|Z| 0.01 Hz) can be used to assess the overall anti-corrosive behavior of an organic coating system, while the charge transfer resistance (R ct ) indicates the resistance to a flow of charge, electronic or ionic, which is inversely proportional to the corrosion rate underneath the coating and its enhancement is associated with self-healing effects (Zhang et al, 2004;Zheludkevich, 2009;Borisova et al, 2013;Meng et al, 2015;Njoku et al, 2017;Ubaid et al, 2019). Figure 6 illustrates the Bode diagrams of (a) the impedance plot vs. frequency and (b) the phase angle diagram vs. the frequency resulting from the exposure of intact coatings to artificial sea water (ASTM D 1141-98) over a period of 223 days.…”
Section: Electrochemical Studiesmentioning
confidence: 99%